2021
DOI: 10.2967/jnumed.120.261503
|View full text |Cite
|
Sign up to set email alerts
|

The new integrated nuclear medicine and radiology residency program in the Netherlands: why do residents choose to subspecialize in nuclear medicine and why not?

Abstract: To explore reasons that influence a resident's choice for the nuclear medicine subspecialty in the integrated nuclear medicine and radiology residency program in the Netherlands. MethodsA web questionnaire was developed and distributed among residents in the Dutch integrated nuclear medicine and radiology training. ResultsA total of 114 residents were included. The survey results revealed four categories of incentives to choose the nuclear medicine subspecialty: 1) Expertise of nuclear medicine physicians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In a study published in the current issue of The Journal of Nuclear Medicine, Velleman et al surveyed 114 residents to better understand their motivations for or against joining the nuclear medicine subspecialty (2). Only a few respondents were nuclear medicine trainees.…”
mentioning
confidence: 99%
“…In a study published in the current issue of The Journal of Nuclear Medicine, Velleman et al surveyed 114 residents to better understand their motivations for or against joining the nuclear medicine subspecialty (2). Only a few respondents were nuclear medicine trainees.…”
mentioning
confidence: 99%
“…More than 5 years have elapsed since its implementation, which provides the opportunity to evaluate firsthand, and independently from the organizing professional societies, the experiences from nuclear medicine physicians and radiologists who work in hospitals that offer this integrated training program. Previous research has identified factors that influence a resident’s choice to start the NMMR subspecialty of the integrated training, but experiences from nuclear medicine physicians and radiologists about the integrated training are still lacking [ 5 ]. This information may be useful to identify strengths of the program that may be emulated by other national societies who consider developing a similar program, and on the other hand, identify potential areas for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…We also agree that nuclear medicine is much more than hybrid imaging, and we strongly believe in the multidisciplinary nature of our field. Interestingly, even the small numbers mentioned in the paper of Velleman et al (1) show a tendency for residents who chose nuclear medicine to be more academic and interested in research, ensuring the future of the vivid research landscape in nuclear medicine in The Netherlands.…”
mentioning
confidence: 99%
“…The paper of Velleman et al. ( 1 ) provides a snapshot, taken mid-2020, based on a sample of less than one third of Dutch residents, with only 9 respondents from the nuclear medicine subspecialty program. Because of these small numbers, the results have to be interpreted with care.…”
mentioning
confidence: 99%
See 1 more Smart Citation